Metaverse? No, thanks! Exploring the mechanisms behind Generation Z’s resistance behavior - Ding, Ning; Hu, Liling; Zhao, Qin; Kim, Kyung-Tae; Chen, Maowei (Frontiers in Psychology, 2025)
The metaverse is progressively advancing toward broad application in real-world scenarios. However, as a key driving force of today’s digital economy, Generation Z has not demonstrated sufficient enthusiasm for participation. This study adopts a mixed-methods approach to systematically explore the resistance behaviors of Generation Z toward the metaverse and their underlying causes. In the first phase, grounded theory was employed to analyze data from 25 in-depth interviews. Through three levels of coding, seven key resistance factors were identified: interpersonal alienation, psychological burden, social norm conflict, value doubt, perceived complexity, perceived unavailability, and perceived risk. In the second phase, structural equation modeling (SEM) was used to examine the net effects of these factors on resistance behavior. The results indicate that all factors except perceived complexity have a significant positive influence on resistance behavior. In the third phase, fuzzy-set qualitative comparative analysis (fsQCA) was employed to identify nine configurations of conditions that lead to resistance, thus addressing the limitations of SEM in capturing complex causal relationships. This study not only extends the theoretical boundaries of user behavior research in the metaverse context but also provides empirical insights for platforms aiming to optimize user experience and develop operational strategies targeted at Generation Z.